1985
DOI: 10.1161/01.res.56.5.718
|View full text |Cite
|
Sign up to set email alerts
|

"Fade" of hyperpolarizing responses to vagal stimulation at the sinoatrial and atrioventricular nodes of the rabbit heart.

Abstract: SUMMARY. Previous studies have suggested that maintained vagal stimulation or acetylcholine infusion results in a fade of responses in the sinoatrial node but not in the atrioventricular node, implying different muscarinic receptor subtypes in the two regions. We investigated this hypothesis in 23 isolated rabbit atrial preparations made quiescent by continuous superfusion with verapamil (1 jtg/ml). Transmembrane potentials were recorded simultaneously from cells in the sinoatrial pacemaker region and from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…In contrast to the situation for I KACh , I Ca,L elicited by the +20 mV voltage step phase of the voltage protocol decreased monotonically with 1 μM ACh application (not shown), declining by 41.7 ± 6.0% ( n  = 6) of its initial amplitude by ∼2 min following the peak I KACh response. The biphasic nature of the fade of AVN cell I KACh in this study correlates qualitatively with a reported biphasic decline of hyperpolarising response of the rabbit intact AVN to trains of vagal nerve stimuli [20], although in absolute terms the time-course of the observed fade of the intact node membrane potential response was faster than that seen here [20]. Differences in time-course of response decline between that study and this one are likely to be accounted for by the different preparations used (intact tissue versus isolated cell) and mode and duration of vagal activation (vagal nerve stimulation versus sustained superfusion of ACh).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In contrast to the situation for I KACh , I Ca,L elicited by the +20 mV voltage step phase of the voltage protocol decreased monotonically with 1 μM ACh application (not shown), declining by 41.7 ± 6.0% ( n  = 6) of its initial amplitude by ∼2 min following the peak I KACh response. The biphasic nature of the fade of AVN cell I KACh in this study correlates qualitatively with a reported biphasic decline of hyperpolarising response of the rabbit intact AVN to trains of vagal nerve stimuli [20], although in absolute terms the time-course of the observed fade of the intact node membrane potential response was faster than that seen here [20]. Differences in time-course of response decline between that study and this one are likely to be accounted for by the different preparations used (intact tissue versus isolated cell) and mode and duration of vagal activation (vagal nerve stimulation versus sustained superfusion of ACh).…”
Section: Resultssupporting
confidence: 87%
“…For example, in one study the negative dromotropic response of anaesthetised dogs to tonic vagal stimulation was reported to exhibit fade when the initial response to vagal stimulation was large [18], whilst in a separate study dromotropic effects of ACh in anaesthetised dogs were reported not to fade during maintained cholinergic activation [19]. On the other hand, vagal stimulation of rabbit isolated atrial preparations from which SAN and AVN responses were monitored simultaneously has been reported to produce membrane hyperpolarization that exhibited similar fade in both regions [20]. We have recently observed transient activation in isolated AVN myocytes of a tertiapin-Q sensitive inwardly rectifying I KACh -like current by the peptide hormone ET-1 [21].…”
Section: Introductionmentioning
confidence: 97%
“…ACh binds to the muscarinic receptors in atrial cells to cause activation of an inwardly rectifying K+ current which contributes to the hyperpolarization and the slowing of the heart rate. Earlier studies have shown that the ACh-induced increase in K+ conductance progressively fades or desensitizes even with maintained vagal or ACh stimulation (Jalife et al 1980;Salata & Jalife, 1985;Carmeliet & Mubagwa, 1986;Kurachi et al 1987). The desensitization of the K+ current response of ACh occurs in two phases; a rapid initial phase lasting approximately 20-30 s and a subsequent slower phase that continues for many minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Such "fading" of the cardiac responses has been attributed to postjunctional effects, such as desensitization of the muscarinic receptors (JALIFE et al, 1980;TOKIMASA et al, 1980;SALATA and JALIFE, 1985) or other mechanisms (GERTJEGERDES et al, 1979;MARTIN et al, 1982). Recently, we observed the fade of the cardiac responses to parasympathetic nerve stimulation in the isolated, perfused dog atrium .…”
mentioning
confidence: 79%